The timeless wisdom of Hinduism: Its impact on philosophy, ethics, and contemporary society - Sunkad, Gayatri (Journal of Language, Literature, Social and Cultural Studies, 2025)
Hinduism is considered the oldest religion in the world, predating even the Vedic civilization. Unlike other major religions with a specific founder—such as Prophet Muhammad for Islam or Jesus Christ for Christianity—Hinduism has no singular originator. Instead, it is often referred to as Sanatana Dharma, meaning "eternal religion." This study aims to explore the historical development, core principles, and global influence of Hinduism while addressing common misconceptions. The research employs a document study approach, analysing primary sources such as the Vedas, Upanishads, Ramayana, Mahabharata, and Bhagavad Gita, along with secondary sources including academic journals and historical texts. A qualitative thematic analysis is used to interpret the philosophical, spiritual, and ethical aspects of Hinduism. Findings indicate that Hinduism has significantly shaped various philosophical and religious traditions worldwide. The Vedas, comprising Rigveda, Samaveda, Yajurveda, and Atharvaveda, serve as the foundation of Hindu thought. The Upanishads expand on metaphysical concepts, while the Puranas and epics provide moral and spiritual guidance. Hinduism’s adaptability has enabled it to integrate with changing social landscapes while maintaining its core teachings. It has influenced global discourses on meditation, yoga, and mindfulness, attracting scholars and practitioners across cultures. In conclusion, Hinduism is not merely a religion but a way of life that harmonizes material existence with spiritual enlightenment. Its philosophical depth, ethical teachings, and emphasis on moksha (liberation) continue to inspire individuals globally. However, misconceptions—such as its association with rigid caste hierarchies—necessitate further scholarly engagement to present a balanced understanding. As the world's most ancient religion, Hinduism remains a living tradition that evolves while preserving its spiritual essence.